Down to the wire - Usdin, Carly (The Avant-Guards, 2020)
THE FINAL SHOT. Everything<U+2019>s happening - Liv & Charlie figuring out what it means to be Liv & Charlie, the final game of the season is here, creating the perfect fundraiser and everyone<U+2019>s parents showed up to cheer them on during the most stressful time the team could imagine. It<U+2019>s Just A Lot For Everyone To Deal With. Luckily the entire existence of the league doesn<U+2019>t depend on this one game or the Avant-Guards winning, right? Oh wait... Acclaimed writer Carly Usdin (Heavy Vinyl: Riot on The Radio) and artist Noah Hayes (Wet Hot American Summer) conclude their hit series about falling in love and finding your team on & off the court.